2016
DOI: 10.1530/endoabs.44.oc3.3
|View full text |Cite
|
Sign up to set email alerts
|

Post-Radioiodine Graves' Management: The Pragma-Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Significant weight gain was observed with treatment, and male gender, black or Hispanic ethnicity and T3 levels at diagnosis were found to be independent predictors of weight rise, whereas age, cause of hyperthyroidism, post‐treatment TSH, compliance and insurance status were not . The PRAGMA study, a multi‐centre, retrospective UK study which included 812 patients who underwent RAI for Graves' disease showed that hypothyroidism developed in two‐thirds of the patients during the first 1 year, with 11% still found to be biochemically hypothyroid at 12 months . Frequent weight gain was reported, affecting about two‐thirds of patients, but with the risk being attenuated in those patients who were commenced on ATDs together with L‐T4 post‐therapy .…”
Section: Weight Changes Due To Hyperthyroidismmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant weight gain was observed with treatment, and male gender, black or Hispanic ethnicity and T3 levels at diagnosis were found to be independent predictors of weight rise, whereas age, cause of hyperthyroidism, post‐treatment TSH, compliance and insurance status were not . The PRAGMA study, a multi‐centre, retrospective UK study which included 812 patients who underwent RAI for Graves' disease showed that hypothyroidism developed in two‐thirds of the patients during the first 1 year, with 11% still found to be biochemically hypothyroid at 12 months . Frequent weight gain was reported, affecting about two‐thirds of patients, but with the risk being attenuated in those patients who were commenced on ATDs together with L‐T4 post‐therapy .…”
Section: Weight Changes Due To Hyperthyroidismmentioning
confidence: 99%
“…64 The PRAGMA study, a multi-centre, retrospective UK study which included 812 patients who underwent RAI for Graves' disease showed that hypothyroidism developed in two-thirds of the patients during the first 1 year, with 11% still found to be biochemically hypothyroid at 12 months. 65 Frequent weight gain was reported, affecting about two-thirds of patients, but with the risk being attenuated in those patients who were commenced on ATDs together with L-T4 post-therapy. 65 Another recurring theme that is evident from these studies is that the development of hypothyroidism is likely to be at least partly to blame for the weight gain observed with hyperthyroidism treatment modalities.…”
Section: Risk Factors For Excessive Weight Gain With Hyperthyroidismentioning
confidence: 99%
See 1 more Smart Citation